PENINGKATAN KUALITAS GONDORUKEM DENGAN VARIASI KONSENTRASI TERPENTIN PADA PENCUCIAN GETAH PINUS - Syaifuddin, Afif; Sa'diyah, Khalimatus; Prasetya, Desta Enggar Dwi (BRIN Publishing, 2025)
Gum rosin, commonly called gondorukem, is a product derived from processing pine sap, possessing significant potential for international market competition. However, the demand for exports from Indonesia has decreased annually due to the gondorukem's quality not meeting market standards. This study investigates the impact of turpentine concentration in the pine resin washing process on the quality of the produced gondorukem. The research was conducted in two stages: sap purification and distillation. In the sap purification process, 1250 grams of pine sap were dissolved using turpentine at 80°C, with varying turpentine concentrations of 27.5%, 28.5%, 29.5%, 30.5%, 31.5%, 32.5%, and 33.5%. This was followed by adding 5% oxalic acid, precipitation for 30 minutes, washing with distilled water, and separation. The washed oleo pine resin, weighing 1100 grams, was then distilled at 175°C for 2-3 hours. Results indicate that higher concentrations of turpentine lead to increased acid value, softening point, and color scale, resulting in purer and darker gondorukem. However, adding turpentine tends to reduce yield while causing fluctuations in nonvolatile parameters. The highest quality gondorukem was obtained at a turpentine concentration of 29.5%, with the following specifications: acid value of 191.24 mg KOH/gram, color scale of 6.9 (WW quality), softening point of 79°C, nonvolatile content of 99.23%, and yield of 75.08%.